Collision Resolution MAC Algorithm for Vehicular Ad Hoc Networks - (:unkn) unknown (IEEE, 2016)
In Vehicular Ad Hoc Networks (VANETs), efficient use of the control channel affects both safety applications that use the control channel and other applications that use the service channels. Its efficiency deteriorates due the collisions on accessing to the control channel or due to the merging collisions which happen when fast moving vehicles use the same allocated channels. In this paper, we propose an algorithm which predicts the possible merging collisions due to the overtaking of fast vehicles. It predicts the collisions within 2-hops neighborhood and recommends the vehicle to acquire a new time slot in the control channel. Through simulations, it is shown that proposed approach reduces the merging collisions.
Keywords: MAC; 802.11p; WAVE; collisions; TDMA; VANET